Diversity and Abundance of Macroinvertebrates in Kaakkaithivu coastal waters, Jaffna estuary - Vithusha, A.; Piratheepa, S. (University of Jaffna, 2021)
This study analyzed the diversity and abundance of aquatic macroinvertebrate community in the Kaakkaithivu coastal waters, Jaffna estuary. The sampling was carried out from July 2018 to January 2019. A total of 459 individuals of 15 macroinvertebrate families belonging to 20 taxa were identified based on their morphological characteristics by using standard keys. They are Coelenterates, Molluscs and Arthropods. According to the Shannon Weiner (H) and Simpson (D) indices, the highest species diversity value and abundance were found at the site-3 (H-2.7163, D-0.0836 and abundance-222) followed by site-2 (H-2.0511, D-0.1688 and abundance-143) and site-1 (H-1.2978, D-0.5822 and abundance- 94). Terebralia palustris (21.35%) and Cerithidea cingulata (20.05%) were the most abundance species belonging to the family Potamididae whereas the least abundant species were Cypraea sp and Metopograpsus sp (0.65% each) at Kaakkaithivu coastal waters.
Keywords: Abundance; Coastal waters; Diversity; Estuary; Macroinvertebrates